2021
DOI: 10.1002/jhet.4214
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopic studies, theoretical aspects, and X‐ray analysis of xanthenodiones (1,8‐dioxooctahydroxanthenes)

Abstract: Compounds containing a pyran moiety fused to two cyclohexen‐2‐one rings are collectively called xanthenodiones (1,8‐dioxooctahydroxanthenes). With the aim of increasing the knowledge about the structures of xanthenodiones, in the present investigation two xanthenodiones, namely 9‐(4‐hydroxy‐3‐methoxyphenyl)‐3,4,5,6,7,9‐hexahydro‐1H‐xanthene‐1,8(2H)‐dione (1) and 9‐(4‐hydroxyphenyl)‐3,6‐diisopropyl 3,4,5,6,7,9‐hexahydro‐1H‐xanthene‐1,8(2H)‐dione (2), were synthesized. Their structures were investigated by nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The reported 3,6-dimethyl-9-phenyl-9-trifluoromethyl-9 H -xanthene-2,7-diol was used as an intermediate in the obtaining quinone-hydroquinone hybrid structures in stereodynamic redox reactions . Furthermore, only a handful of studies focused on the structure of xanthenes derivatives have been reported, for example, the 9-substituted-9-xanthenol clathrates studied by Taljaard and co-workers, , the 1,8-dioxooctahydroxanthenes analyzed by da Silva and collaborators, the 9-substituted-9-phenylxanthenes reported by Kavala and others, or mechanochemical cocrystallization of fluorescein by Bučar and others …”
Section: Introductionmentioning
confidence: 99%
“…The reported 3,6-dimethyl-9-phenyl-9-trifluoromethyl-9 H -xanthene-2,7-diol was used as an intermediate in the obtaining quinone-hydroquinone hybrid structures in stereodynamic redox reactions . Furthermore, only a handful of studies focused on the structure of xanthenes derivatives have been reported, for example, the 9-substituted-9-xanthenol clathrates studied by Taljaard and co-workers, , the 1,8-dioxooctahydroxanthenes analyzed by da Silva and collaborators, the 9-substituted-9-phenylxanthenes reported by Kavala and others, or mechanochemical cocrystallization of fluorescein by Bučar and others …”
Section: Introductionmentioning
confidence: 99%